Rainfall and economic growth and poverty: Evidence from Senegal and Burkina Faso - Cabral, Joseph François (International Food Policy Research Institute, 2014)
This paper assesses the effects of rainfall shocks on poverty in Burkina Faso and Senegal using a computable general equilibrium model. An index quantifying effects of rainfall fluctuations shows that, due to a predicted increase in annual rainfall, Senegal will experience a decline in poverty, while Burkina Faso will experience an increase in its poverty rate in conjunction with a trend of declining rainfall. The implementation of mitigating policies in Burkina Faso can affect the rate of increase in poverty, but future rainfall trends are expected to have positive effects on poverty in Senegal and negative effects in Burkina Faso.